(untitled) (Journal of Engineering Science, 2020)
Mg, Cu and Zn metals have been used to tri-dope into the tetrahedral and octahedral sites of Li4Ti5O12 (LTO) electrode materials usually used in Li-ion battery. Li4-xMgxTi5-yZny/2Cuy/2O12 (i. x = 0, y = 0 ii. x = 0.05, y=0.10 iii. x= 0.10, y= 0.20 iv. x= 0.15, y= 0.20) materials were synthesized by solid state reaction using the stoichiometric amount of raw materials. The structural and morphological characteristics of the tri-doped Li4-xMgxTi5-yZny/2Cuy/2O12 materials were methodically analyzed by using Fourier transform infrared spectroscopy (FT-IR), UV-visible spectroscopy, thermogravimetric analysis (TGA), X-ray diffraction (XRD), scanning electron microscopic (SEM) techniques. The results of infrared spectroscopy exhibit bands of TO6 octahedra and Ti-O-Ti vibrations. Band gap energy calculation from UV-visible spectroscopy demonstrates a critical point of doping. Beyond this point band gap energy has been found to increase upon tri-doping. It has been observed from SEM images that all samples possess micro-porous and coral shape structures. The XRD patterns demonstrate that Mg, Cu and Zn metals tri-doped Li4-xMgxTi5-yZny/2Cuy/2O12 materials have spinel structure as well as good crystallinity. Journal of Engineering Science 11(1), 2020, 01-08